1998
DOI: 10.1071/zo97033
|View full text |Cite
|
Sign up to set email alerts
|

An electrophoretic comparison of the Australian paralysis tick, Ixodes holocyclus Neumann, 1899, with I. cornuatus Roberts, 1960 (Acari : Ixodidae)

Abstract: An electrophoretic study was conducted on ticks morphologically identified as either Ixodes cornuatus or I. holocyclus from Tasmania and several localities on mainland Australia. Ticks were characterised genetically at 27 enzyme loci encoding 24 enzymes. The extent of genetic divergence (52–69% fixed differences) between ticks from Tasmania and those from the mainland was equivalent to that found between these two groups and two morphologically distinct species, I. hirsti and I. fecialis. The Tasmanian ticks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It has been suggested that ticks from different geographic regions secrete toxin at different rates and volumes . Genetic variation among individual ticks, which was assessed using electrophoresis of multiple enzyme loci, is so marked that some authors have suggested that I. holocyclus could be a complex of several species and this could underscore differential rates of toxin production.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ticks from different geographic regions secrete toxin at different rates and volumes . Genetic variation among individual ticks, which was assessed using electrophoresis of multiple enzyme loci, is so marked that some authors have suggested that I. holocyclus could be a complex of several species and this could underscore differential rates of toxin production.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, differences in toxin production or toxin content, possibly related to genetic variation within I. holocyclus might offer an alternative explanation 30 . Three neurotoxins (holocyclotoxins: HT‐1, HT‐2, HT‐3) have been recently isolated from I. holocyclus 31 and genetic studies using multilocus enzyme electrophoresis suggest that I. holocyclus is not a single species, but represents a complex of two or more species that can coexist in the same geographic location 32,33 . Hence, different subspecies of I. holocyclus , existing in sympatry, might secrete a different battery of neurotoxins with varying local and general effects, thereby providing a plausible explanation as to why some ticks which cause TP produce unilateral facial paralysis and others at similar sites of attachment do not.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson et al (1998) also found substantial differences between I. holocyclus and I. cornuatus: variation at 52-69% of allozyme loci studied. More recently, Jackson et al (2000) found that up to 80% of allozyme loci studied varied between I. holocyclus and I. cornuatus.…”
Section: Discussionmentioning
confidence: 82%
“…However, Penglis (1987) was unable to find differences in oviposition period, egg-incubation time or in other aspects of reproduction of I. holocyclus between highland and lowland areas of south-east Queensland. Jackson et al (1998; studied variation in I. holocyclus and I. cornuatus at 24-27 allozyme loci and found that the two species were genetically distinct. In addition, Jackson et al (2000) found preliminary evidence that I. holocyclus may represent a species complex.…”
Section: Introductionmentioning
confidence: 99%